Development of Self-Regulatory Design Based on Local Cultural Values in Adolescents - Bau Ratu; Nurwahyuni Nurwahyuni; Herlina Herlina; Ratman Ratman; Irmawati Musa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Drug abuse, especially among adolescents, is a big problem in Indonesia. One of the preventive efforts against drug abuse is to increase adolescent assertive behavior in refusing drug abuse. This study aims to (1) increase adolescent assertive behavior in resisting drug abuse through sel-fregulation based training Siri' na Pacce, and (2) identify differences in assertive behavior between male and female adolescents. The subject is class VIII students of SMPN 2 Turatea, Jeneponto Regency, South Sulawesi for the academic year 2020/2021 138 students, including 20 boys and 18 girls aged 12 to 15 years were selected as the research sample which was determined by purposive sampling technique (non-randomized sample). The research instrument was a questionnaire of assertive behavior in refusing drug abuse modified from the Drug Refusal Assertiveness Scale (DRAS) developed by Wills and Botvin (1989). This study uses a quasi-experimental Non-Equivalent Control Group Design (pre-test and post-test). The data analysis method is an analysis of covariance (ANCOVA). The research results show that the training is self-regulation based Siri' na Pacce has a significant effect on increasing adolescent assertive behavior in refusing drug abuse. In addition, female students are shown to have higher scores in assertive behavior than male students. This is related to active participation in self-regulation training, where female students are more active so they can understand the training material better and faster.Abstrak: Penyalahgunaan narkoba khususnya di kalangan remaja merupakan salah satu masalah besar di Indonesia. Salah satu upaya preventif terhadap penyalahgunaan narkoba adalah dengan meningkatkan perilaku asertif remaja dalam menolak penyalahgunaan narkoba. Penelitian ini bertujuan untuk (1) meningkatkan perilaku asertif remaja dalam menolak penyalahgunaan narkoba melalui pelatihan self-regulation berbasis Siri' Na Pacce, dan (2) mengidentifikasi perbedaan perilaku asertif antara remaja pria dan wanita. Subyeknya adalah.siswa kelas VIII SMPN 2 Turatea Kabupaten Jeneponto Sulawesi Selatan tahun pelajaran 2020/2021 sebanyak 138 siswa, termasuk 20 laki-laki dan 18 perempuan berusia 12 sampai 15 tahun dipilih sebagai sampel penelitian yang ditentukan dengan teknik Purposive sampling (non-randomized sample). Instrumen penelitian berupa angket perilaku asertif dalam menolak penyalahgunaan narkoba yang dimodifikasi dari Drug Refusal Assertiveness Scale (DRAS) yang dikembangkan oleh Wills and Botvin (1989). Penelitian ini menggunakan quasi eksperimen desain Non-Equivalent Control Group Design (pre-test and post-test). Metode analisis data adalah analisis kovarians (ANCOVA). Hasil penelitian menunjukkan bahwa pelatihan self-regulation berbasis Siri' Na Pacce berpengaruh signifikan terhadap peningkatan perilaku asertif remaja dalam menolak penyalahgunaan narkoba. Selain itu, siswa perempuan terbukti memiliki skor yang lebih tinggi dalam perilaku asertif dibandingkan siswa laki-laki. Hal ini terkait dengan partisipasi aktif dalam pelatihan self-regulation, dimana siswa perempuan lebih aktif sehingga mereka dapat memahami materi pelatihan dengan lebih baik dan lebih cepat.